Tailoring Content for Authenticity and Adoption: Community-Based Participatory Research and the Co-creation of Story-Based Health Communication for Underserved Communities - Villar, Maria Elena; Johnson, Paige W. (Frontiers in Communication, 2021)
This perspective presents concrete examples of how community-based participatory research can be used effectively to decolonize health communication through the co-creation of health communication content specifically tailored to minoritized and underserved communities. The authors describe how community members and researchers partnered to conduct community listening, observation and co-create stories to be used in fotonovelas (graphic stories), radio stories, serious games and community theater. Community members are experts on their experiences and can best translate those experiences into stories that ring true for target audiences from similar backgrounds. Truly participatory research grounded in community values can be slow and take unexpected turns, but it is critical to create health communication content that resonates with audiences and contributes to influencing attitudes and behaviors. When Community-Based Participatory Research (CBPR) is used in true collaboration with the community, marginalized communities, which were historically exploited by community researchers, can become the architects of their own health outcomes.